Beyond Agency and Structure: Triple-Loop Learning - Yuthas, Kristi (Journal of business ethics, 2004)
With the demise of Andersen, LLP and new legislation that puts an end to self-governance in public accounting, the effectiveness of current models of accounting ethics have been seriously called into question. We argue that the profession suffers from fundamental limitations in its ethical framework that makes it impossible to effectively address ongoing ethical problems. The dominant representation of professional behavior is an agency model of ethics, in which the ultimate responsibility for identifying and dealing with ethical dilemmas resides with the individual. We argue that structural forces such as control over resources, meaning systems, and community norms and values also have a strong influence on the actions of accountants and that these must also be considered. The recent legitimation crisis has forced the accounting profession and its constituencies to begin to recognize and address the structural aspects of ethics as they enable and constrain action. We propose a framework based on structuration theory and learning theory that allows for systematic, multi-level investigation of the structural forces that cause ethical dilemmas to arise and to be recognized and that influence the manner in which they are analyzed and resolved. This framework should be capable of continual critique and reconfiguration as environmental conditions change.